THE LEVEL OF TEACHER'S FEEDBACK IN ENGLISH TEACHING: AN EFL CLASSROOM DISCOURSE ANALYSIS - Aisyah, Aisyah; Wicaksono, Bayu Hendro (Celtic: A Journal of Culture, English Language Teaching, Literature and Linguistics, 2020)
The objectives of this research are to know the level of feedback applied by the EFL teacher at a junior high school in speaking class and to know the most frequent level of feedback employed by the EFL teacher. Moreover, this research conducts a qualitative research where the data of this research are the English teacher’s utterances when the teacher taught speaking for VII grade students at one of state junior high school at Sentani, Papua. Meanwhile, the data was gathered through observing and transcribing the video of English teaching and learning process. The analysis of the transcript revealed that: (1) there arethree levels of feedbacks employed by the teacher: feedback of task (6.25%), feedback of process (37.5%), and feedback of self as a person (56.25%) and (2) the most frequent level of feedback employed by the teacher is the feedback of self as a person since it gathered 56.25% during the teaching and learning activity. Based on the result of this study, it can be concluded that teacher’s feedback is an important tool to facilitate the learning process become more active. Therefore, It is suggested the teacher may use more collaboration of feedback toward students’ response or performance in the learning process.